PENGARUH KUALITAS PRODUK DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN DAN DAMPAKNYA TERHADAP MINAT BELI KEMBALI (Studi pada Pelanggan Mobil Mitsubishi Mirage di Kota Semarang) - Yogie Febry Arzaqi Tikananda, 11.05.51.0058; Basiya, Robertus (Students Journal of Economic and Management, 2016)
The purpose of this study was to analyze the effect of product quality and service quality to customer satisfaction and its impact on consumer buying interest back to the car Mitsubishi mirage in Semarang. This study uses three hypotheses. The population of this study is that people who buy cars Mitsubishi Mirage in Semarang. The sample in this study as many as 100 people. The sampling technique used purposive sampling. The criteria for the sample in this study is that consumers who buy and use cars Mitsubishi Mirage at least one year. The analysis tool used is multiple linear regression. The results of the analysis can be concluded that: The product quality and significant positive effect on customer satisfaction. Quality of service is positive and significant impact on customer satisfaction. Consumer satisfaction is positive and significant impact on consumer buying interestKeywords: product quality, service quality, customer satisfaction and buying interest back.Â